Physiological action of bioherbicides in weed control: a systematic review - Zhang, Zhenglin; Becerra-Alvarez, Aaron; Al-Khatib, Kassim (Frontiers in Agronomy, 2025)
IntroductionBioherbicides are naturally derived substances that can be used to control weeds. Bioherbicide compounds can be alternatives to synthetic herbicides and are key resources for the discovery of novel molecules and modes of action (MOA) for weed control. To better understand the physiological action of bioherbicides, a systematic review was conducted with an emphasis on understanding the MOA of bioherbicides.MethodsA systematic review screened 287 studies of published literature. The review retained seventeen studies that demonstrated evidence of bioherbicide mode of action.ResultsFrom our review, we found that bioherbicides are often a mixture of various substances and potentially have multiple MOAs. Compound mixtures present in bioherbicides intrinsically increase the difficulty level in elucidating the mechanistic causation for plant injury. The majority of empirical studies reported injury to weeds at the plant, tissue, or cell level - but were unable to define specific biological pathways affected by bioherbicide application. In total, seventeen studies had strong evidence for specific MOAs, including photosystem II inhibition, microtubule synthesis inhibition, carotenoid synthesis inhibition, cellular metabolism inhibition, and auxin mimics.DiscussionHypothesis driven research, chemical characterization, gene expression, and molecular in-silico modeling were important steps in identifying the MOA and should be considered in future studies. It was not uncommon to observe bioherbicide compounds with evidence for more than one MOA. With a better understanding of bioherbicides and their herbicidal action, increased efficacy can be achieved and catalyze novel product development.